Perceived Parental Monitoring and Online Deviant Behavior in Adolescents: Mediated by Dark Triad Traits - Rea, Lee; Izzaty, Rita Eka (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2025)
This study aimed to investigate the mediating role of dark triad traits in the relationship between perceived parental monitoring and online deviant behavior among adolescents in Yogyakarta. A quantitative method was used, and data were collected from 308 adolescents aged 13 to 18 years and analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS). The results showed that dark triad traits partially mediated the effect of perceived parental monitoring on online deviant behavior. Specifically, the indirect influence of perceived parental monitoring on online deviant behavior was mediated by machiavellianism (17.6%), narcissism (3.5%), and psychopathy (3.8%). Furthermore, increased perceived parental monitoring could reduce the tendency toward dark triad personality traits, thereby lowering the incidence of online deviant behavior among adolescents. This study recommended that parents improved their supervision to strengthen perceived parental monitoring, thereby reducing dark triad traits and preventing online deviant behavior.